Effectiveness of Executive Auction Responsibility as A Problem Credit Settlement in PT.Bank Mandiri (Persero) Tbk Purwokerto Area - Adhitya Zaputra (Authentica, 2018)
This paper is intended to analyze the effectiveness of the implementation of the auction of Hak Tanggungan as an effort to resolve non performing loan at PT. Bank Mandiri (Persero) Tbk Purwokerto Area, based on the data obtained in the field of 158 the number of troubled debtors throughout 2017, only 6 debtors have successfully auctioned. The low level of auction behavior is due to many factors both internal and external factors that occur before the implementation or after the implementation of the auction. This paper uses the empirical approach method, namely the effort to approach the problem under study with the nature of the law that is real or in accordance with the reality that lives in society. Based on Lawrence M Friedman's theory, the implementation of auctions is not effective, the biggest factors that influence are substance and cultural factors, namely the rules regarding emptying of collateral for auction behavior and the people who are afraid of having problems buying assets by auction. Therefore, rules must be reinforced to guarantee auction buyers to avoid problems in the future after the collateral is sold. Keywords: effectiveness; auction; settlement of non performing loans; inhibiting factors